Cell‐Specific Dysregulation of Iron and Oxygen Homeostasis as a Novel Pathophysiology in PSP. Issue 3 (30th November 2022) - Lee, Seojin; Martinez‐Valbuena, Ivan; de Andrea, Carlos E.; Villalba‐Esparza, Maria; Ilaalagan, Suganthini; Couto, Blas; Visanji, Naomi P.; Lang, Anthony E.; Kovacs, Gabor G.
Abstract : Objective: Progressive supranuclear palsy (PSP) is a 4R‐tauopathy showing heterogeneous tau cytopathology commencing in the globus pallidus (GP) and the substantia nigra (SN), regions also associated with age‐related iron accumulation. Abnormal iron levels have been extensively associated with tau pathology in neurodegenerative brains, however, its role in PSP pathogenesis remains yet unknown. We perform the first cell type‐specific evaluation of PSP iron homeostasis and the closely related oxygen homeostasis, in relation to tau pathology in human postmortem PSP brains. Methods: In brain regions vulnerable to PSP pathology (GP, SN, and putamen), we visualized iron deposition in tau‐affected and unaffected neurons, astroglia, oligodendrocytes, and microglia, using a combination of iron staining with immunolabelling. To further explore molecular pathways underlying our observations, we examined the expression of key iron and oxygen homeostasis mRNA transcripts and proteins. Results: We found astrocytes as the major cell type accumulating iron in the early affected regions of PSP, highly associated with cellular tau pathology. The same regions are affected by dysregulated expression of alpha and beta hemoglobin and neuroglobin showing contrasting patterns. We discovered changes in iron and oxygen homeostasis‐related gene expression associated with aging of the brain, and identified dysregulated expression of rare neurodegeneration with brain iron accumulation (NBIA) genes associated with tau pathology to distinguish PSP from the healthy aging brain. Interpretation: We present novel aspects of PSP pathophysiology highlighting an overlap with NBIA pathways. Our findings reveal potential novel targets for therapy development and have implications beyond PSP for other iron‐associated neurodegenerative diseases. ANN NEUROL 2023;93:431–445